2015
DOI: 10.1002/mnfr.201400799
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid metabolites reduce tumor necrosis factor‐α secretion to a greater extent than their precursor compounds in human THP‐1 monocytes

Abstract: ScopeFlavonoids are generally studied in vitro, in isolation, and as unmetabolized precursor structures. However, in the habitual diet, multiple flavonoids are consumed together and found present in the circulation as complex mixtures of metabolites. Using a unique study design, we investigated the potential for singular or additive anti‐inflammatory effects of flavonoid metabolites relative to their precursor structures.Methods and resultsSix flavonoids, 14 flavonoid metabolites, and 29 combinations of flavon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 61 publications
4
71
1
Order By: Relevance
“…Peak metabolite signatures appeared to have biological activity, despite the extremely low concentrations of their individual constitutes. Here responses were often greater then activities previously reported by our group for the same metabolites in isolation or in mixtures at equal molar concentrations . Previous studies have explored this concept of physiologically relevant concentrations of metabolite profiles by applying extracted serum/plasma to cell culture models.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Peak metabolite signatures appeared to have biological activity, despite the extremely low concentrations of their individual constitutes. Here responses were often greater then activities previously reported by our group for the same metabolites in isolation or in mixtures at equal molar concentrations . Previous studies have explored this concept of physiologically relevant concentrations of metabolite profiles by applying extracted serum/plasma to cell culture models.…”
Section: Discussionmentioning
confidence: 69%
“…Traditionally, in vitro studies have explored the activity of parent anthocyanins mechanistically, however their low plasma concentrations and rapid clearance kinetics suggests they are not the bioactive forms responsible for in vivo activity. It is therefore probable that anthocyanin bioactivity in vivo results from the lesser studied, though more bioavailable, phenolic metabolites, and we have recently demonstrated they are more active on inflammatory biomarkers than their precursor structures .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have already observed an antinociceptive activity of other glycosides of this flavonol, mainly over the inflammatory pain [48, 49]. The antioxidant and anti-inflammatory activities of the p -hydroxybenzoic acid have already been described previously [50, 51]. In relation to its potential antinociceptive effect, it is interesting to note that the p -hydroxybenzoic acid is an isomer of the salicylic acid, a molecule widely used for pain treatment [52].…”
Section: Discussionmentioning
confidence: 91%
“…Microbial metabolites are more bioactive than the parent compounds in in vitro models exerting greater vascular and antiinflammatory activity than the metabolites formed and absorbed in the small intestine (Amin et al 2015;de Ferrars et al 2014;di Gesso et al 2015;Krga et al 2016). Together, these data provide further evidence that the bioactivity of anthocyanins is highly likely attributed to their microbially-derived metabolites, which are present in the circulation significantly longer and at much higher levels than the parent anthocyanins (Czank et al 2013;de Ferrars et al 2014).…”
Section: Is Metabolism Key To Clinical Efficacy Of Anthocyanins and Dmentioning
confidence: 96%